Contrast-enhanced angiographic computed tomography for detection of aneurysm remnants after clipping: a comparison with digital subtraction angiography in 112 clipped aneurysms - Gölitz, Philipp; Struffert, Tobias; Ganslandt, Oliver Thomas; Lang, Stefan; Knossalla, Frauke; Dörfler, Arnd (Neurosurgery, 2014)
For preclusion of remnants after aneurysm clipping, a reliable, noninvasive imaging technique is desirable.To evaluate the reliability of optimized angiographic computed tomography with intravenous contrast agent injection (ivACT) in detecting remnants after aneurysmal clipping compared with digital subtraction angiography (DSA), the gold standard.We included 84 patients with 112 clipped cerebral aneurysms of the anterior circulation. For treatment, 116 clips of cobalt and 57 clips of titanium alloy were used. In each patient, we performed an ivACT with dual rotational acquisition and a DSA. Data from ivACT were postprocessed with a dual-volume technique with newly implemented reconstructions modes. Aneurysm remnants were measured, classified, and correlated with DSA by 2 raters.In total, 12 remnants were revealed by DSA, meaning a prevalence of 11%. IvACT demonstrated a sensitivity of 75% to 92% and a specificity of 99% in detecting remnants up to a minimal size of 0.7 × 0.3 mm. Classification of remnants by ivACT was identical to that by DSA, and assessment of size showed a significant correlation with DSA (P < .001). No significant differences between cobalt and titanium alloy were revealed concerning artifacts.Optimized ivACT with enhanced postprocessing demonstrated high sensitivity and specificity in detecting remnants after aneurysm clipping in the anterior circulation. Classification and assessment of remnant size and detection of relevant parent artery stenosis showed high accuracy of ivACT compared with DSA. Our results indicate that ivACT might become a noninvasive alternative to DSA for postsurgical control.
EVALuna2:22328